Perceptions of food environments in the school and at home during Covid-19: An online cross-sectional study of parents, teachers and experts from Latin America (2023)
ABSTRACT: Background The high prevalence of overweight and obesity in children from Latin America (LA) have been related to obesogenic food environments. Besides, the negative effects of the Covid-19 pandemic should also be considered. The objective of this research was to describe and compare the perceptions of parents, teachers, and experts in LA of food environments at home and school that favor healthy habits in schoolchildren in pre Covid-19 stage and during the pandemic. Methods This study used a survey self-reporting regarding conditions at home and the school favoring healthy habits, for three profiles: parents, primary school teachers, and experts. A fisher exact test was used to establish the difference between the response categories between countries and profiles. Logistic regression models were used to determine the probability of response in the levels of importance adjusted for sex and nationality. Results Information from 954 questionnaires was reported: 48.4% experts, 32.0% teachers, and 19.6% parents. There were differences in the perception of food environments at school between profiles (p<0.001). In multivariate logistic regression models, experts and teachers were 20% more likely to give greater importance to elements of the food environment at school compared to parents (p<0.001). Conclusions Our findings showed that parents were less likely to perceive important elements of the school food environment compared to experts and teachers. Interventions are required to improve healthy eating environments that consider children’s interpersonal mediators.